Condizionamenti morfologici e geologici dei terreni nelle scelte costruttive degli edifici per spettacoli. Riflessioni su alcuni anfiteatri dell’Italia romana - Trivelloni, Ilaria (O T I V M, 2020)
The aim of this study is to underline the strict connection that exists between a building and the shape of the terrain where it has been erected. The slope to adapt at least one part of the cavea to the natural landscape, remained one of the most important elements in the selection of the most suitable area for their construction. The analysis, focused on the amphitheaters built in Roman Italy, has shown that also the geological formation is one of the fundamental elements in construction choices. Due to the examples analysed in this paper it has been possible to divide the cases between those built on dominant morphologies and those apparently unrelated to the geography of the site. For these, a detailed examination of the geological maps of the terrains, where self-supporting amphitheaters are built, has shown that the construction choices reflect the geological characteristics of the soils.